Research and Applications in Operations Management: Discussion of a Paradox - Smith, Robert D.; Robey, Daniel (Academy of Management Journal, 1973)
The purpose of this article is to identify apparent inconsistencies between research and application in the field of Production/Operations Management. The authors focus on three key areas: Assembly Line Balancing, Scheduling, and Information Systems. Research topics and pedagogical recommendations incorporating a more systemic approach to the field are suggested.